COveRs to impRove AesthetiC ouTcome after Surgery for Chronic subdural haemAtoma by buRr hole trepanation (CORRECT-SCAR): protocol of a Swiss single-blinded, randomised controlled trial - Martin N Stienen; Kevin Akeret; Flavio Vasella; Julia Velz; Elisabeth Jehli; Pierre Scheffler; Stefanos Voglis; Oliver Bichsel; Nicolas Roydon Smoll; Oliver Bozinov; Luca Regli; Menno R Germans; et al. (BMJ Open)
Introduction Outcomes rated on impairment scales are satisfactory after burr hole trepanation for chronic subdural haematoma (cSDH). However, the surgery leads to bony defects in the skull with skin depressions above that are frequently considered aesthetically unsatisfactory by the patients. Those defects could be covered by the approved medical devices (burr hole covers), but this is rarely done today. We wish to assess, whether the application of burr hole covers after trepanation for the evacuation of cSDH leads to higher patient satisfaction with the aesthetical result at 90 days postoperative, without worsening disability outcomes or increasing the complication rate.Methods and analysis This is a prospective, single-blinded, randomised, controlled, investigator-initiated clinical trial enrolling 80 adult patients with first-time unilateral or bilateral cSDH in Switzerland. The primary outcome is the difference in satisfaction with the aesthetic result of the scar, comparing patients allocated to the intervention (burr hole cover) and control (no burr hole cover) group, measured on the Aesthetic Numeric Analogue scale at 90 days postoperative. Secondary outcomes include differences in the rates of skin depression, complications, as well as neurological, disability and health-related quality of life outcomes until 12 months postoperative.Ethics and dissemination The institutional review board (Kantonale Ethikkommission Zürich) approved this study on 29 January 2019 under case number BASEC 2018–01180. This study determines, whether a relatively minor modification of a standard surgical procedure can improve patient satisfaction, without worsening functional outcomes or increasing the complication rate. The outcome corresponds to the value-based medicine approach of modern patient-centred medicine. Results will be published in peer-reviewed journals and electronic patient data will be safely stored for 15 years.Trial registration number NCT03755349.